Deep sea nature-based solutions to climate change - Hilmi, Nathalie; Sutherland, Michael; Farahmand, Shekoofeh; Haraldsson, Gunnar; van Doorn, Erik; Ernst, Ekkehard; Wisz, Mary S.; Claudel Rusin, Astrid; Elsler, Laura G.; Levin, Lisa A. (Frontiers in Climate, 2023)
The deep sea (below 200 meters depth) is the largest carbon sink on Earth. It hosts abundant biodiversity and provides provisioning, supporting, regulating and cultural ecosystem services. There is growing political attention to climate-regulating ocean ecosystem services. In this essay, we synthesize the unique biophysical, socioeconomic, and governance characteristics of the deep sea to critically assess opportunities for deep-sea blue carbon to mitigate climate change. Deep-sea blue carbon consists of carbon fluxes and storage including carbon transferred from the atmosphere by the inorganic and organic carbon pumps to deep water, carbon sequestered in the skeletons and bodies of deep-sea organisms, carbon buried within sediments or captured in carbonate rock. However, mitigating climate change through deep-sea blue carbon enhancement suffers from tipping points (no long-term solution), technological limitations, a lack of cooperation and collaboration, and implementation. Together, these issues suggest that deep-sea climate change mitigation is limited. Thus, we suggest that a strong focus on blue carbon is too limited a framework for managing the deep sea to contribute to international goals, including the SDGs, the Paris Agreement, and the post-2020 Biodiversity Goals. Instead, the deep sea can be viewed as a more holistic nature-based solution, including many ecosystem services and biodiversity in addition to climate. Environmental impact assessments, area-based management, pollution reduction, moratoria, carbon accounting, and fisheries management are tools in international treaties could help realize benefits from deep-sea nature-based solutions.